ANALISIS STRATEGI PENGEMBANGAN BAITUL MAAL WAT TAMWIL (BMT) DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT DI SUMATERA SELATAN - Ratna (LA RIBA: Jurnal Perbankan Syariah, 2020)
This study aims to describe the development conditions of BMT, analyze the strategy of developing BMT as a savings and loan cooperative and Islamic finance in the city of southern Sumatera, and analyze the role of BMT in improving the welfare of surrounding communities. The data used in this study are primary data obtained from the observation process and some interview processes. The analysis is carried out by descriptive analysis method based on the theory obtained through library studies. The results of this study indicate that BMTs are now alive and well is BMT who continues to make improvements. The strategy used to adjust conditions, which part should be strengthened and supported so that customers remain loyal to BMT; and BMT has a role, among others, is to keep the community away from the moneylenders or usury, invites the public to entrust their money to BMT, the micro business community is invited to be more disciplined in managing the financial results of their business, and help people who are just starting a business, or whose business is already running in financing, so that the business can grow and develop, so that prosperity will be achieved.